PARTISIPASI PEREMPUAN DALAM PENGELOLAAN LINGKUNGAN - Irma Irma; Marlina Marlina; Badriani Badawi (UNM Environmental Journals, 2022)
Women and the environment are one unit. Starting from the cosmetic products they use to waste from domestic work affecting the environment. The role and contribution of women in managing and protecting the environment is very important. This study aims to find out how women's participation in protecting the environment. Information from this study was obtained using a survey method on women who are members of environmental care groups. The sampling technique uses saturated samples. The respondents were all members of the women's group caring for the environment totaling 25 people. The results of this study show that young and educated women are more active in participating. This is because of the drive in them to protect the environment. To increase their participation, they need to get education about the use of good and correct cosmetics so as not to overdo it.